1885 Ill. Rev. Stat. 192 - (:unkn) unknown (My University, 1885)
An Act to Protect Cemeteries and to Provide for their Regulation and Management, § 1: That any person who shall willfully destroy, mutilate or injure any tomb, monument, stone, vault, tree, shrub or ornament, or any object whatever, in any cemetery, or in any avenue, lot or part thereof, or shall hunt, shoot or discharge any gun, pistol or other missile, with the limits of any cemetery, or shall cause any shot or missile to be discharged into or over any portion thereof, or shall violate any of the rules made and established by the board of directors of such cemetery§
Keywords: DISCHARGE